IFN-gamma regulation of ICAM-1 receptors in bronchial epithelial cells: soluble ICAM-1 release inhibits human rhinovirus infection - Spiteri Monica A; Whiteman Suzanne C (BMC, 2008)
Abstract Background Intercellular adhesion molecule-1 (ICAM-1) is a critical target-docking molecule on epithelial cells for 90% of human rhinovirus (HRV) serotypes. Two forms of ICAM-1 exist, membranous (mICAM-1) and soluble (sICAM-1), both expressed by bronchial epithelial cells. Interferon-gamma (IFN-γ), a crucial Th-1 immuno-regulatory mediator, can modulate mICAM-1 expression; however its simultaneous effects on mICAM-1: sICAM-1 levels and their consequent outcome on cell infectivity have not been previously explored. Methods Primary normal human bronchial epithelial cells were pre-stimulated with IFN-γ (1 ng/ml for 24 h) and subsequently inoculated with HRV-14 or HRV-1b (TCID50 10 2.5). Epithelial surface ICAM-1 expression and soluble ICAM-1 release were measured at the protein and gene level by immunofluorescence and ELISA respectively; mRNA levels were semi-quantified using RT-PCR. Molecular mechanisms regulating ICAM-1 isoform expression and effects on epithelial cell infectivity were explored. Results In IFN-γ-biased cells infected with HRV-14, but not HRV-1b, mICAM-1 expression is down-regulated, with simultaneous induction of sICAM-1 release. This differential effect on HRV-14 receptor isoforms appears to be related to a combination of decreased IFN-γ-induced JAK-STAT signalling and proteolytic receptor cleavage of the membranous form in IFN-γ-biased HRV-14 infected cells. The observed changes in relative mICAM-1: sICAM-1 expression levels are associated with reduced HRV-14 viral titres. Conclusion These findings support the hypothesis that in epithelial cells conditioned to IFN-γ and subsequently exposed to HRV-14 infection, differential modulation in the ratio of ICAM-1 receptors prevails in favour of an anti-viral milieu, appearing to limit further target cell viral attachment and propagation.